Stopping power of Zn for heavy ions - Cantero, E.D. (2012)
We present stopping power measurements of Zn for C and O ions and compare them with a theoretical description given by the Transport Cross Section - Extended Friedel Sum Rule (TCS-EFSR) for the valence electrons, and two different models for the inner-shells: the Shellwise Local Plasma Approximation (SLPA) and the CasP approach. The SLPA, which successfully applies to projectiles from H to B, is slightly high for C ions and clearly overestimates the data for O ions. On the other hand, total stopping results using the CasP description for the inner-shells show good agreement with the data for C and O ions, and also with the SRIM predictions. © Published under licence by IOP Publishing Ltd.